Analisis kontribusi pembiayaan mudharabah dan murabahah terhadap pendapatan operasional bank syariah - Nurjannah, Novia Rosi (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2016)
The purpose of this study was to determine the apalication of mudharaba and murabaha financing on BMI and the contributions made financing on operating revenues of bank as well as assessing the financial performance of bank through the financial statements and evaluating the suitability of the application that was done BMI with PSAK 105 and 102. This study used descriptive qualitative approach, namely by looking at the financial reports of 2014 and conducted interviews. This research was to know the implementation of murabaha and mudharaba financing to operating income as well as assessing the financial performance and evaluating the suitability of the application done BMI with PSAK 105 and 102. The results of this research shows that the implementation of murabaha and mudharaba financing provided funds to customers for investments and sold goods. Mean while the bank’s contribution to the operating income of the profit/ margin derived of financing. BMI operating income obtained from various bank products and services. Financial performance that was measured by financial ratios indicated that the value of ROA was well under the Bank Indonesia regulation and BOPO ratio values can be concluded that the effeciency of operational costs incurred by the bank in good condition and not in a state of trobled banks. The accounting treatment of murabaha and mudharaba financing which included presentation, measurement, disclosure adn recognition carried BMI in Accordance with the application of PSAK 102 and 102.